A geometric morphometric study of a Middle Pleistocene cranium from Hexian, China. Issue 88 (November 2015) - Cui, Yaming; Wu, Xinzhi
Abstract: The Hexian calvarium is one of the most complete and well-preserved Homo erectus fossils ever found in east Asia, apart from the Zhoukoudian specimens. Various methods bracket the age of the Hexian fossil to between 150 and 412 ka (thousands of years ago). The Hexian calvarium has been considered to be H. erectus given its morphological similarities to Zhoukoudian and Javan H. erectus . However, discussion continues regarding the affinities of the Hexian specimen with other H. erectus fossils. The arguments mainly focus on its relationships to other Asian H. erectus fossils, including those from both China and Java. To better determine the affinities of the Hexian cranium, our study used 3D landmark and semilandmark geometric morphometric techniques and multivariate statistical analyses to quantify the shape of the neurocranium and to compare the Hexian cranium to other H. erectus specimens. The results of this study confirmed the morphological similarities between Hexian and Chinese H. erectus in overall morphology, and particularly in the structure of the frontal bone and the posterior part of the neurocranium. Although the Hexian specimen shows the strongest connection to Chinese H. erectus, the morphology of the lateral neurocranium resembles early Indonesian H. erectus specimens, possibly suggesting shared common ancestry or gene flow from early Indonesian populations. Overall cranial and frontal bone morphology are strongly influenced by geography. Although geographically intermediate between Zhoukoudian and Indonesian H. erectus, the Hexian specimen does not form part of an obvious morphological gradient with regard to overall cranial shape.